Suitability of Surface Water for Domestic Water Use - Korfali, S. I. (2011)
The Arab Region is currently challenged by securing sufficient water resources for sustainable development. Although, Lebanon is considered relatively “the reservoir of water in the Middle East”, still, the provision of adequate, sustainable safe domestic water remains a major challenge to be met. The city of Beirut hosts one third of the Lebanese population due to progressive urbanization, resulting mostly from centralization of services and economic activities. Faced with this challenge, the tendency is to reduce dependency on groundwater resources and supplement it by surface water. The Awali River is among the 16 perennial flowing water resources, at a relatively convenient distance from the Capital (Beirut). The objective of this work is to evaluate the river water basin to determine the optimal extraction points, water quality variability and the need to develop and sustain proper river basin management and quality control programs. Accordingly, water samples were collected throughout the year from identified sampling locations. Complete physical, chemical, microbiological (pH, Conductivity, TDS, TOC, Ca, Mg, HCO3, SO4, NO3, Na, K, Fe, Zn, Cu, Pb, Cd, Mo, Co, Total Coliform, Ecoli ) quality profile based on standard methods and procedures were conducted. Further data was analysed using SigmaStat statistical package and water modelling software AquaChem. Preliminary results reflect on minimal exposure to sources of pollution other than domestic sewage. This further emphasizes the need to meet the water and sustainable goals of the water for life decade 2005-2015. Moreover, promoting and sustaining water and sanitation projects becomes a real challenge